Detection of the disease-associated form of the prion protein in biological samples. (January 2015) - Nicholson, Eric M
Transmissible spongiform encephalopathies (TSEs) are neurodegenerative diseases that occur in a variety of mammals. In TSEs, a chromosomally encoded protein (PrP C ) undergoes a conformational change to the disease-associated form (PrP d ). PrP d is capable of inducing a change in additional molecules of PrP C to the PrP d conformation. TSEs are inevitably fatal and cross-species transmission is known to occur, and there is potential for transmission via blood transfusion and organ transplantation in humans. Thus, there is interest in high-quality diagnostics for both humans and animals. This review summarizes methods of TSE detection currently in use in diagnostic settings and discusses recent advances in PrP d detection that afford substantial enhancements in sensitivity over currently approved methods for use in clinical settings.